Analyzing the Economic Impact of Marketing Mix Strategies on Entrepreneurial Resilience - Machda Citra Nabila Syah; Anita Sumelvia Dewi (International Journal of Economics Development Research (IJEDR), 2025)
In this study, This study aims to examine the marketing mix strategies and entrepreneurial challenges faced by UMKM Warung_Nasii. The research employs a qualitative approach using phenomenological methods to explore the subjective experiences of business actors in depth. Data were collected through in-depth interviews with the business owner and supporting informants, as well as direct observation of business activities at the outlet and during Car Free Day events. The findings reveal that the 7P marketing mix strategies (product, price, place, promotion, people, process, and physical evidence) are applied adaptively by Warung_Nasii in responding to the dynamics of the culinary market. Product variations are achieved through menu innovation, pricing strategies are adjusted to consumer purchasing power, location strategies combine permanent outlets with participation in CFD events, and promotion is carried out through social media and direct customer interaction. However, the study also identifies several significant challenges, such as limited capital, fluctuations in raw material prices, increasingly intense business competition, limited human resources, and operational time management. From a phenomenological perspective, these challenges are not merely obstacles but also shape adaptive strategies that strengthen business resilience. This research contributes to the development of MSME marketing strategy literature by providing empirical insights into the application of the marketing mix alongside the dynamics of entrepreneurial challenges. The findings are expected to serve as a reference for other culinary MSMEs in formulating innovative, contextual, and sustainable marketing strategies.